“Planning for Voice” to help women to exercise agency - Kosec, Katrina; Kyle, Jordan; Nayarayan, Sudha; Raghunathan, Kalyani (CGIAR System Organization, 2024)
Planning for voice: A novel approach to help women develop the skills they need to exercise voice and agency in their communities.